RETRACTED: The Effect of Productive Safety Net Programme on Household Food Consumption and Dietary Diversity in Ethiopia - Feyisa, Mebratu Negera (Frontiers in Sustainable Food Systems, 2022)
This study empirically investigates the effect of productive safety net programme (PSNP) on household food consumption and dietary diversity in Ethiopia. The study applied random effects with instrumental variable to estimate the effect of PSNP membership. The result of the study indicates that though membership to PSNP program improves household food consumption, it reduces household dietary diversity score. Moreover, household food consumption and dietary diversity are also significantly influenced by sex, age and education status of household head, household size, livestock ownership, distance to the nearest market and participation in non-farm activities. The findings of this study suggest that membership to PSNP program household should be complemented with building households’ awareness about benefits associated with the consumption of variety of food items. In addition, PSNP membership should be designed to endow the households to accumulate essential assets, especially livestock.